Attitudes toward carrier screening and prenatal diagnosis for recessive hereditary deafness among the educated population in urban China. Issue 12 (11th August 2016) - Fu, Xiaoli; Cai, Yi; Hu, Yechen; Liu, Jisheng; Yang, Tao
Abstract : Approximately 80% of hereditary deafness is recessive, in which case most mutation carriers were unaware of their carrier status. Though parental attitudes toward genetic testing and prenatal diagnosis are overall positive in those with deaf children, there is little information about that in the general population. To this end, we designed a self‐completed questionnaire and distributed it in two colleges in Shanghai, China. A total of 975 completed surveys were returned in print or online forms. Our results showed that 98.7% of the respondents without family history of early onset deafness did not know or underestimated their likelihood to carry a recessive mutation in common deafness genes. After brief written information was given using GJB2, the most common recessive deafness gene as the example, 67.7% of the respondents expressed interest in knowing if they are carriers of GJB2 mutations through genetic testing. In hypothetical circumstance of carrying a recessive GJB2 mutation, 86.9% would suggest their partners to also take the test. In case that both were carriers, 88.7% would consider prenatal diagnosis and 80.7% would consider terminating an affected pregnancy. On the basis of these results, it was concluded that despite the poor awareness to the risk of recessive hereditary deafness, the majority of the educated population in urban China likely hold a positive view toward carrier screening and prenatal diagnosis of recessive deafness genes. © 2016 Wiley Periodicals, Inc.